Smart toaster machine / Najwatul Hasanah Zamani - Zamani, Najwatul Hasanah (2014)
Smart Toaster Machine is a device that use toaster and forward motor. The toaster has two condition which are medium and well done. When the toasting process is done, the buzzer will sound and the motor will eject the bread and tray come out from the toaster. It indicate that the bread is ready.